1998
DOI: 10.1142/s0219246298000138
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Resettlement Difficulties: A Qualitative Analysis of Coping Strategies Used by Mainland Chinese Immigrants in Hong Kong

Abstract: A qualitative study was undertaken to explore the coping strategies used by mainland Chinese immigrants in Hong Kong to handle psychosocial stressors experienced during the resettlement stage of the migration process. It was revealed that coping strategies employed were stage-specific and culture-specific. While problem-solving strategies and compromise were used by immigrants to deal with recurring, daily resettlement difficulties, cognitive strategies of positive comparisons and positive and optimistic think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although migrants may have experienced stress initially when arriving in Hong Kong, they are reluctant to expand or mobilize their social network beyond their immediate family community. As Wong (1997) shows, Mainland Chinese immigrants face tremendous difficulties in establishing friendships with Hong Kong natives and therefore have extremely limited friendship networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although migrants may have experienced stress initially when arriving in Hong Kong, they are reluctant to expand or mobilize their social network beyond their immediate family community. As Wong (1997) shows, Mainland Chinese immigrants face tremendous difficulties in establishing friendships with Hong Kong natives and therefore have extremely limited friendship networks.…”
Section: Discussionmentioning
confidence: 99%
“…First, the measurement of social networks was not fully comprehensive because a very important aspect of social network analysis, the frequency of contact, was not assessed. Second, previous work has shown that when immigrants encounter any problems in Hong Kong, they mainly turn to their existing friends or kin in Mainland China for social support (Chow and Ho, 1996; Lai, 1997; Wong, 1997, 2001). However, this study assessed only the social support available in Hong Kong and did not cover the network maintained in Mainland China.…”
Section: Discussionmentioning
confidence: 99%
“…dents studying in Hong Kong's tertiary institutions (Pan, 2008;Yi & Tsang, 2010;Cheung, 2013;Zhang, 2015;Yu & Zhang, 2016) and newly arrived immigrants from Chinese mainland (Chan, 2001;Chou, 2009;Hung, 2002;Chan, 2013). While these studies have contributed to our understanding of the acculturation experiences of mainland students in Hong Kong, they have also shed light on the significance of sociolinguistic interactions with locals (Gu, 2011;Zhang, 2015) and the role of communication accommodation in facilitating cross-cultural adaptation (Song & Shan, 2016). Furthermore, the moderating role of social support in the acculturation and cross-cultural adaptation of these students has been explored (Lian & Tsang, 2010;Ng, Wang, & Chan, 2017).…”
Section: Research On the Driftersmentioning
confidence: 99%
“…Most existing research on discrimination against and exclusion of Mainland immigrants, as well as their resistance and resilience, focuses on lower-middle-class women, often with limited education, who are married to lower-class Hong Kong men and reside in Hong Kong on the basis of the one-way permit scheme (Law and Lee, 2006;Ng et al, 2015;Wong, 1998;Yu et al, 2014). Student migrants from mainland China, even though they share the same place of birth as well as some cultural characteristics like not speaking Cantonese, belong to a different category for immigration purposes.…”
Section: Chinese Student Migrants and Political Participationmentioning
confidence: 99%